IMPLEMENTASI METODE QIROATI DALAM PEMBELAJARAN AL-QUR’AN - Hetty Mulyani; Maryono Maryono (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2019)
This research was aimed 1) to describe an implementation of the qiroati method in learning of al quran, 2) to describe techniques of usage of qiroati method in learning of al quran, 3) to describe the support and handicap factors in learning of al quran. The method of research used a qualitative method. Qualitative method is a research method based on positivism philoshopy that used to research the naturalistic phenomena. Technique of data collection used a participant observation, depth interview and study of ducument. Test of data validatity used a triangulation technique and data analysis used an interactive analysis of mile and huberman that ie data collection, data reduction, data display and conclusion/verifying. Result of research showed that 1) implementatuon of the qiroati method in learning of al quran have three steps such as planning step, implementating step and evaluation step. 2) technique of teaching the qiroati method in learning of al quran that were the sorogan technique, the individual class and the class of reading&hearing. and 3) there were three support factors such self student, conusive environment and good hard & soft ware and handicap factors that ie peer and companies, curicullum and external motivation.